Design of Intelligent Polyhouse with IOT - Bedi, Harpreet Singh; Harshin, Ambu Naga; Lawai, BP; Kumar, Neeraj (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
A polyhouse, often known as a greenhouse, is a building constructed for the controlled growing of plants. It is often built of translucent materials such as glass or plastic and is intended to offer a regulated temperature for plants, shielding them from harsh weather but allowing sunlight to pass through. The study considers various factors such as affordability and feasibility, combines IoT and fuzzy control techniques, uses GPRS for remote control, and creates a smart greenhouse monitoring system that is user-friendly, simple to operate, and performs well. Moreover, there are automated control mechanisms, such as greenhouse doors and windows that roll on and off in response to soil moisture levels. By using IoT to maintain precise parameters like CO2, soil moisture, temperature, and light in the greenhouse, the technology will help farmers increase productivity while reducing the need for physical field visits. An internet connection and an IoT kit are used for the task. The bell pepper plant's greenhouse conditions include CO2, soil moisture, temperature, and light